Effects of different early rehabilitation techniques on haemodynamic and metabolic parameters in sedated patients: protocol for a randomised, single-bind, cross-over trial. Issue 1 (30th January 2017) - Medrinal, Clément; Combret, Yann; Prieur, Guillaume; Robledo Quesada, Aurora; Bonnevie, Tristan; Gravier, Francis Edouard; Frenoy, Éric; Contal, Olivier; Lamia, Bouchra
Abstract : Introduction: Early rehabilitation has become widespread practice for patients in intensive care; however, the prevalence of intensive care unit-acquired weakness remains high and the majority of physiotherapy is carried out in bed. Several inbed rehabilitation methods exist, but we hypothesise that techniques that provoke muscle contractions are more effective than passive techniques. Methods: A randomised, controlled cross-over study will be carried out to evaluate and compare the effectiveness of early rehabilitation techniques on cardiac output (CO) in sedated patients in intensive care. 20 intubated and sedated patients will undergo 4 10 min rehabilitation sessions. 2 sessions will involve 'passive' techniques based on mobilisations and inbed cycle ergometry and 2 involving electrostimulation of the quadriceps muscle and Functional Electrical Stimulation-cycling (FES-cycling). The primary outcome is CO measured by Doppler ultrasound. The secondary outcomes are right ventricular function, pulmonary systolic arterial pressure, muscle oxygenation and minute ventilation during exercise. Results and conclusion: Approval has been granted by our Institutional Review Board (Comité de Protection des Personnes Nord-Ouest 3). The results of the trial will be presented at national and international meetings and published in peer-reviewed journals. Trial registration number: NCT02920684.